Recruitment Strategies for Encouraging Participation in Corporate Volunteer Programs - Peterson, Dane K. (Journal of business ethics, 2004)
Perhaps due to the numerous community and company benefits associated with corporate volunteer programs, an increasing number of national and international firms are adopting such programs. A major issue in organizing corporate volunteer programs concerns the strategies that are most effective for recruiting employee participation. The results of this study suggest that the most effective strategies for initiating participation in volunteer programs may not be the same as the strategies that are most effective in terms of maximizing the number of volunteer hours contributed by employees. More importantly, the results suggest that the most effective recruitment strategies depend on the age of the employee. The results were discussed in terms of matching the recruitment strategies with the characteristics of the potential volunteers and the nature of the volunteer project.